Antecedents of organizational citizenship behavior nurse type c hospital Surabaya - Wibowo, Teguh Setiawan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze the OCB antecedents of type C hospital nurses in Surabaya. This research uses quantitative research with a case study approach. Data analysis techniques in this study used validity, reliability, classical assumption and hypothesis testing. Based on the results of data analysis and discussion, it can be seen that the OCB antecedent of Type C Hospital nurses in the city of Surabaya is influenced by several factors, including the Thriving Workplace variable and the Person-Organizational Fit variable that does not have a significant influence on the Organizational Citizenship Behavior of Type C Hospital nurses in the city. Surabaya. Meanwhile, Organizational Commitment variable has a positive and significant influence on Organizational Citizenship Behavior. The addition of the Job Embededness variable has an effect, so that the three variables of Thriving Workplace, Person-organization Fit, and Organizational Commitment have a positive and significant influence on the Organizational Citizenship Behavior of Type C Hospital nurses in the city of Surabaya. While the intervening variable represented by Job Embededness also has a positive and significant influence on Organizational Citizenship Behavior of Type C Hospital nurses in the city of Surabaya.